Associação entre caracterização antropométrica e desempenho de nadadores jovens nos diferentes estilos e provas de natação - Borges, Dayanne Sarah Lima (2021)
In swimming, the kinanthropometric determinants reflected in performance are still poorly studied, but they can be an important factor in sports performance. Therefore, the study aimed to identify the anthropometric pattern and performance of young swimmers (12 to 17 years old) in different swimming (crawl, backstroke, breaststroke, and butterfly) and in different events (50m, 100m, 200m, 400m, 800m, and 1500m). For this, 123 athletes, 75 male (15.4 ± 1.1 years) and 48 female (15.7 ± 1.2 years), from the cities of Campo Grande (32) (MS), Belo Horizonte (57) (MG), and Curitiba (34) (PR) were cross-sectionally evaluated in two stages (anthropometric characterization and performance tests). In the freestyle, power had a positive relationship with height (r = 0.71) and with the perimeters of the abdomen (r = 0.60), forearm (r = 0.81), and leg (r = 0.71). For the breaststroke, the power ratio with forearm perimeter was r = 0.79. Similarly, the backstroke also obtained expressive values for the relationship between power and height (r = 0.85), chest perimeter (r = 0.79), waist (r = 0.90), abdomen (r = 0 .86), thigh (r = 0.80) and leg (r = 0.77). The female group had similar relationships. The results demonstrate an interaction between the physical capacities for the athletes' performance. That is, the work of all variables is transferable to a real performance gain. There is a highlight for the freestyle results: male sprinters (50 to 200m) and half long distances (400m) are wide, strong, and powerful. Butterfly swimmers for sprint events have smaller heights and body mass. Backstroke swimmers are tall, broad, and powerful. Female sprinters (50 and 100m) are tall, wide, and powerful, unlike long-distance swimmers. Considering the swimming, butterfly swimmers have broad shoulders and an emphasis on strength and endurance. In the backstroke, they are tall and powerful, and in the freestyle, they are wide, tall, light, and resistant. The present study allowed the identification of anthropometric and performance patterns in a representative sample of young swimmers at national level. Therefore, different swims have different anthropometric characteristics that are associated with physical performance, with emphasis on muscle power.